Factors associated with disease‐free and abdominal recurrence‐free survival in abdominopelvic and retroperitoneal sarcomas. Issue 8 (3rd March 2022) - Bredbeck, Brooke C.; Delaney, Lia D.; Kathawate, Varun G.; Harter, Cameron A.; Wilkowski, Jodi; Chugh, Rashmi; Cuneo, Kyle C.; Dossett, Lesly A.; Sabel, Michael S.; Angeles, Christina V.
Abstract: Background and Objectives: Retroperitoneal and abdominopelvic sarcomas are rare heterogeneous malignancies. The only therapy proven to improve disease‐free survival (DFS) is R0/R1 surgical resection. We sought to analyze whether additional factors such as radiation and systemic therapy were associated with DFS and abdominal recurrence‐free survival (RFS). Methods: Retrospective review of adults (≥18) with resectable abdominopelvic and retroperitoneal sarcomas who underwent intent‐to‐cure surgery at a high‐volume tertiary referral center between 1998 and 2015. The main outcome measures were DFS and abdominal RFS. Results: Overall, 159 patients met the criteria for inclusion. Median follow‐up was 4.8 years (range 0.1–18.9 years). The most common histology was liposarcoma (49%). Systemic therapy was administered to 48% of patients and was not associated with improved outcomes. The neoadjuvant radiotherapy group (11%) had improved adjusted DFS (5.46 years, 95% CI [3.68, 7.24] vs. 3.1 years, 95% CI [2.48, 3.73]) and abdominal RFS (6.14 years, 95% CI [4.38, 7.89] vs. 3.22 years, 95% CI [2.61, 3.84]). The adjuvant radiotherapy group (19%) had no improvement. Conclusions: In a cohort of patients undergoing resection for retroperitoneal or abdominopelvic sarcoma, neoadjuvant radiation improved DFS and abdominal RFS. A follow‐up of over three years was needed to appreciate a difference in outcomes.